#### Answer

$y = -3, x = 2$

#### Work Step by Step

$x + y = -1$
$3x + 2y = 0$
$3(x+y) = -1 \times 3$
$3x + 2y = 0$
$3x + 3y = -3$
$3x + 2y = 0$
$3x - 3x + 3y -2y = -3 - 0$
$y = -3$
$3x + 2 \times -3 = 0$
=>$3x -6 = 0$
=>$3x = 6$
=>$x = 2$

Published by
Cengage Learning

ISBN 10:
1-13311-087-8

ISBN 13:
978-1-13311-087-3

$y = -3, x = 2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.